Exploring Public Speaking Anxiety among the First-Year College Students in West Java Indonesia - Halimah, Halimah; Nuraida, Ida (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study aims to examine the level of public speaking anxiety experienced by first-year students at the Faculty of Teacher Training and Education of a private university in Cianjur, West Java, during the 2023/2024 academic year. A quantitative research approach was employed, involving 27 students (21 females and 6 males) aged between 18 and 19 years. Data were collected using a five-point Likert scale questionnaire adapted from McCroskey’s (2009) Personal Report of Public Speaking Apprehension (PRPSA), which consists of 34 statements (12 negative and 22 positive). The collected data were analyzed statistically by calculating the mean and standard deviation to identify patterns and trends in students' public speaking anxiety levels. The findings revealed that 18% of students experienced high levels of public speaking anxiety, 63% reported moderate anxiety levels, and 19% exhibited low anxiety levels. The students experienced both process anxiety and performance anxiety. The results of this study serve as a foundation for developing intervention programs aimed at addressing students' speaking anxiety and enhancing their public speaking skills.